Design of a Useful Diagrammatic Scale for the Quantification of Lecanicillium fungicola Disease in Agaricus bisporus Cultivation - Caitano, Cinthia E. C. [UNESP]; Iossi, Matheus R. [UNESP]; Pardo-Giménez, Arturo; Vieira Júnior, Wagner G. [UNESP]; Dias, Eustáquio S.; Zied, Diego C. [UNESP] (Springer Nature, 2020)
The aim of the research was (i) to evaluate white and cream strains of A. bisporus yields when challenged or not with the pathogen L. fungicola, (ii) to identify the more aggressive pathogen isolates, and (iii) to develop a diagrammatic scale of spot symptoms on infected mushrooms. The experiment was carried out using two strains of A. bisporus (white and cream strains, ABI 19/01 and PB 19/01, respectively) and four isolates of L. fungicola (LF 19/01, FL 19/02, LF 19/03, and LF 19/04). The A. bisporus white strain (ABI 19/01) reached a higher yield of healthy mushrooms compared to the cream strain (PB 19/01) with values of 23.8 and 14.1%, respectively. The LF 19/03 pathogen was most aggressive, reducing the yield of healthy mushrooms by up to 64% for the PB 1/01 strain, and 49.6% for the ABI 19/01 strain. Additionally, for the same isolate, larger mushroom areas were affected, while also displaying symptoms precociously during the second flush. Finally, using the set of visually displayed symptoms assessed in this study, we were able to construct a diagrammatic scale to assist commercial mushroom growers for managing diseased crops.